Prevalence and correlates of physical violence perpetrated by an intimate partner against women who are pregnant in India - Harish Kalra; Thach Tran; Hau Nguyen; Prabha Chandra; Helen Sharp; Jane Fisher (BMC Pregnancy and Childbirth)
Abstract Background Intimate partner violence (IPV) against women is a public health concern and a human rights violation. Women in low- and middle-income countries such as India experience higher rates of violence than in high-income countries. Experiencing IPV during pregnancy is associated with worse maternal, foetal and child outcomes. There is relatively limited representative population-based data on the burden and related factors of IPV experienced by women during pregnancy in India. This study aimed to ascertain the prevalence of experiences of physical IPV during pregnancy and the factors associated with it in India. Methods This is a secondary analysis of data collected in the Fifth Indian National Family Health Survey (NFHS-5). The primary outcome was lifetime experience of physical violence during pregnancy perpetrated by a former and/or current partner. The relationship between this outcome and sociodemographic, relationship, societal and gender-based factors characteristics were examined. Data were analysed using multivariable logistic regression. Results Among 60,579 women who had ever been married or in a union and ever been pregnant, the lifetime prevalence of physical IPV during pregnancy was 2.4%. Experience of physical violence during pregnancy was significantly more common among women experiencing diverse social and economic disadvantages such as low household wealth, being a member of a scheduled caste, or a religious minority. Women whose partners had lower educational status or who drank alcohol had higher odds of experiencing IPV during pregnancy. It was less common among women who were more empowered including having more decision-making autonomy. Conclusion Despite low prevalence, the absolute numbers of women experiencing physical IPV during pregnancy in India are alarmingly high. There is an urgent need to screen and provide early interventions for IPV during pregnancy in India. Further research is needed to identify the prevalence of other forms of intimate partner violence including sexual and emotional abuse, financial abuse and coercive control experienced by women who are pregnant in India.